A Review on Childhood Anxiety - Greeshma, P. V.; Joseph, Theyamma (Innovational: Journal of Nursing and Healthcare, 2024)
This article contains detailed data and review evaluations of the concept of anxiety disorder in children. It is one of the currently facing issues by parents, teachers, and surrounding caretakers, which needs meticulous care and management. It feels like a simple psychological feeling but can lead to complex, unpredictable complications. The causes and risk factors may be varied depends on individuality and background situation. The incidence rate shows tremendous increment, and the related issues show very hike. This complicated situation makes the parents in a big dilemma for managing their children and social reactions. The urbanization, industrialization, and job conditions of parents indirectly influenced for making this feelings as a disorder. Majority of humans, especially children, possess various behavioral patterns during their development to adulthood. Although it is a universal truth and normal for all, when it becomes harmful to themselves and others, it can be considered behavioral disorder. It is a common and normal feeling of psychology and its projection appropriate to the situation shows psychological well-being. Hence, its overness and extremity needed proper identification and management. In psychological theories, it is clearly stated about various reactions of children and even adults. When children fail to pass these steps, which results in various emotional tragedies like anxiety disorder. This article deals with the conditions, including its etiological factors, symptoms, various types of anxiety disorders, and its management, including various review studies regarding this concept.